Tinjauan Yuridis Pasal 56 Kitab Undang-Undang Hukum Acara Pidana Terkait Pemberian Bantuan Hukum Dengan Cuma-Cuma Menurut Perspektif Hak Asasi Manusia - Windra Imanuel Ambarita; Mukhlis R; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In the rule of law, the state guarantees equality before the law and recognizes and protects humanrights, so that all people have the right to be treated equally before the law, as in the provision of legalassistance to suspects or defendants either free of charge. The provision of free legal assistance itself hasbeen regulated in the Kitap Law of Criminal Procedure, which is the basis of formal criminal law inIndonesia. With the existence of Law of the Republic of Indonesia Number 39 of 1999 concerning HumanRights, it makes the interpretation that the Criminal Procedure Code has not been able to providecomprehensive legal assistance so that it can cause a narrowing in the fulfillment of Human Rights inobtaining equality before the law in court. Based on this understanding, the author formulates 2 problemformulations. First, whether the arrangement for the provision of free legal assistance based on Article 56 ofthe Code of Criminal Procedure in Indonesia is in accordance with the perspective of human rights, second,what is the ideal idea of providing free legal assistance to fit the perspective of human rights.This type of research is normative juridical legal research, which is research conducted withliterature review or literature study in searching for data. This research is descriptive in nature that providesdata that is as thorough and detailed as possible on existing problems. In this writing using qualitative dataanalysis which means explaining and concluding about the data that has been collected by the author. Thisresearch uses secondary data or scientific data that has been codified.From the results of this study, it is found that, there is something that can be concluded is that theprovision of free legal assistance as stipulated in article 56 of the Criminal Procedure Code is not thoroughlygiven to suspects or defendants who are considered economically disadvantaged, so that there is a neglect ofhuman rights for those who are not accompanied by legal assistance in trial. In this case, ideal ideas areneeded, such as revising the Criminal Procedure Code or reforming laws by the government so that there areno human rights that are improved, especially in obtaining justice before the law.Keywords: Free Legal Aid-Human Rights